The application of FTIR spectroscopy and chemometrics for classification of Mangosteen extract and its correlation with alpha-mangostin - Abdul Rohman, Fitriana Hayyu Arifah, Irnawati, Gemini Alam, Muchtaridi Muchtaridi (Journal of Applied Pharmaceutical Science, 2020)
Alpha-mangostin is the major component in Mangosteen (Garcinia mangostana Linn) pericarp having several pharmacological activities including reducing blood pressure, antidiabetic, anticancer, and antioxidants. The objective of this study was to develop Fourier transform infrared spectroscopy-multivariate calibration of partial least square (PLS) for quantitative analysis of alpha-mangostin and to classify mangosteen pericarp using principal component analysis. Mangosteen pericarps from different locations (Java provinces and South Sulawesi, Republic of Indonesia) were extracted using ethanol and were subjected to high performance liquid chromatography (HPLC) for the analysis of alpha-mangostin and Fourier transform infrared (FTIR) spectroscopy measurements. HPLC was used to determine the levels of alpha-mangostin and used as actual values during FTIR spectroscopy analysis. The prediction of alpha-mangostin was obtained from the correlation between actual values and FTIR predicted values and facilitated with the PLS model. The results showed that the wavenumbers region of 3,825–937 cm−1 offered a reliable model with a coefficient correlation (r) value of 0.9927 and root mean square error of calibration of 0.0831%. The validation models also exhibited the accurate and precise results for the prediction of alpha-mangostin with an r-value of 0.9754 and root mean square error of prediction value of 0.174%. Furthermore, the chemometrics of principal component analysis using variables of absorbances at selected fingerprint (1,000–800 cm−1) could classify mangosteen pericarp from different regions. FTIR spectroscopy combined with chemometrics offered a reliable method for quality assurance of mangosteen pericarp.
Keywords: Alpha-mangostin, partial least square, principal component analysis, mangosteen pericarp, FTIR spectroscopy.